Susceptibility of Streptococcus pneumoniae to penicillin in the state of Minas Gerais, Brazil from 1997-2004 - Maria B. M. Bedran (Brazilian Journal of Infectious Diseases)
We monitored the susceptibility to penicillin of invasive strains of Streptococcus pneumoniae in two reference laboratories; 502 positive cultures from patients with an active invasive infectious process were analyzed. Streptococcus pneumoniae was identified through conventional procedures, and the oxacillin disc diffusion method was used to check for penicillin susceptibility. Statistical analysis included calculations of the frequency distribution, with 95% confidence intervals (CI), as well as chi-square tests and chi-square for linear trend for temporal analysis of susceptibility. The bacterium was isolated from patients less than a year old (40.7% of the isolates), from infants (55.9%), and from individuals less than 15 years old (64.4%). The majority (88.2%, 95% CI = 85.5%-91.1%) of the 502 isolates were susceptible to penicillin. There was no significant temporal trend of elevation of resistance rate during the study period (p=0.56). We conclude that resistance of S. pneumoniae to penicillin is not yet an important clinical-epidemiological concern in the State of Minas Gerais. To provide necessary support for the adoption of therapeutic and prophylactic measures, epidemiological surveillance should be implemented at a national level to monitor the profile of susceptibility/resistance of S. pneumoniae to penicillin and other antimicrobials.